H.M. Rusli Zainal, S.E., M.P. : sang visioner : konsep dan implementasi dalam membangun Bumi Lancang Kuning : - Tanjung, Adrinal, 1971- (STIA Kawula Indonesia Jakarta, 2008)
Regional development planning and good governance implementation in Riau Province under leadership of Governor Rusli Zainal.